Analisis Faktor-faktor yang Mempengaruhi Potensi Mogok Kerja Karyawan di Yogyakarta - Jemadi Jemadi; Siti Noor Hidayati (Jurnal Maksipreneur, 2012)
Strikes happened in some companies are often caused by employee dissatisfaction. They may disturb production processes and impede the achievement of company goals. Increasing job satisfaction can minimize the strike potential. Job satisfaction is affected by financial, physical, psychological, and social satisfaction factors. It was revealed that financial, physical, psychological, and social satisfaction have statistically significant negative effects on strike potential, with social factor to be the most dominant. Thus, company may implement financial, physical, psychological, and social satisfaction factors to minimize the strike potential.